STUDY OF ADSORPTION ISOTHERMS OF POLAR AND NON-POLAR MOLECULES ON SILICA ADSORBENTS - Jumaeva, Dilnoza; Akhrorova, Rano; Barnoeva , Sayyora; Kodirov, Оrifjon; Raximov, Umidjon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Objective. The purpose of this research work is to study the adsorption isotherms of mesoporous silica adsorbents, their sorption-structural indicators and their relative surface area. Methods. Adsorption isotherms of mesoporous adsorbents were carried out using the quartz spring balance method in the Mac-Ben-Bakra device. Using this method, adsorption isotherms of silica adsorbents synthesized at different temperatures are obtained. Based on this, information is given about their sorption structure characteristics. Results. During the research, the adsorption isotherms of the samples (230/22, 234/22 and 235/22) showed a steep appearance due to the high amount of adsorption P/Ps=0.2 at low relative pressures. The curves of the adsorption isotherm graph of adsorbents showed that they correspond to type IV of the classification proposed by Brunauer. The main absorptions of adsorption of benzene molecules on silica adsorbents: 24.1% in 230/22, 19.7% in 213/22, 24.2% in 234/22, -27.9% in 235/22, -23.9% in 244/22, -21.6% in 245/22. corresponds to the amount of monolayer capacity of adsorbents. Conclusion. Adsorption isotherms were studied in the presence of polar molecule water and nonpolar molecule benzene as adsorbate on silica adsorbents . Based on the isotherm curves of synthesized silica adsorbents, it was determined that they belong to type IV according to Based on the isotherm curves of synthesized silica adsorbents, it was determined that they belong to type IV according to Brunaeer's classification. The sorption-structural characteristics studied during the research and the data obtained on the volumetric pores gave results on their important dimensions such as micro- and meso-porosity, radius size of the pores, as well as the relative surface area.